Видовий склад та динаміка чисельності фітонематод у ризосфері сосни звичайної - Сігарьова, Д.Д.; Місюра, Н.О.; Галаган, Т.О.; Нікішичева, К.С. (Вестник зоологии, 2007)
Исследован комплекс нематод ризосферы сеянцев сосны обыкновенной из питомника Национального аграрного университета. Выявлено 52 вида фитонематод, которые относятся к 3 экотрофическим группам: паразиты растений (7 видов), микофаги (13) и сапробионты (32). Кратность увеличения популяции фитогельминтов в период вегетации была наивысшей для группы фитопаразитических нематод (166–773 ос. в 100 см3 почвы, или в 4,6 раза), средней — для микогельминтов (360–954 ос. в 100 см3 почвы, или в 3 раза), менее низкой — для сапробионтов (от 1143 ос. в 100 см3 почвы в июне до 2282 — в сентябре, или в 2 раза). The complex of nematodes living in rhizosphere of pine seedlings in the nursery of National Agrarian University (Kyiv) was examined. As a result, 52 species of phytonematodes were found; they belong to 3 ecotrophical groups: plant parasites (7 species), mycophagous (13) and saprobiotic nematodes (32). The increasing of populations density during the vegetative season was the highest for the group of plant parasites (166–773 individuals per 100 cm3 of soil, or 4.6 times), the medium — for mycophagous (360–954 individuals per 100 cm3 of soil, or 3 times), and the least — for saprobiotic nematodes group (from 1143 individuals per 100 cm3 of soil in June to 2282 — in September, or twice).